2018
DOI: 10.1038/s41467-018-06370-3
|View full text |Cite
|
Sign up to set email alerts
|

A growing bacterial colony in two dimensions as an active nematic

Abstract: How a single bacterium becomes a colony of many thousand cells is important in biomedicine and food safety. Much is known about the molecular and genetic bases of this process, but less about the underlying physical mechanisms. Here we study the growth of single-layer micro-colonies of rod-shaped Escherichia coli bacteria confined to just under the surface of soft agarose by a glass slide. Analysing this system as a liquid crystal, we find that growth-induced activity fragments the colony into microdomains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
206
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(212 citation statements)
references
References 42 publications
6
206
0
Order By: Relevance
“…Thus, to study the collective motion of twitching mode bacteria, we have developed a distinct model. Nonetheless, our model neglects further biological complications, such as multiple motility modes 40,42,48 , reproduction 54 , biosurfactants 55 , bacteria-secreted polymeric trails 56 and nutrient competition. Incorporation of these effects is left to future work.…”
mentioning
confidence: 99%
“…Thus, to study the collective motion of twitching mode bacteria, we have developed a distinct model. Nonetheless, our model neglects further biological complications, such as multiple motility modes 40,42,48 , reproduction 54 , biosurfactants 55 , bacteria-secreted polymeric trails 56 and nutrient competition. Incorporation of these effects is left to future work.…”
mentioning
confidence: 99%
“…Furthermore, experimental and theoretical studies show the emergence of long-ranged nematic [26][27][28] and polar [29,30] orientational alignments of self-propelled +1/2 defects that, at least theoretically, could even self-organize into positionally ordered lattice structures [27,31,32]. Moreover, the strong flow fields generated by selfpropelled +1/2 defects are shown to drive the formation of protrusions at free surfaces [33,34], dictating the morphology of active multiphase systems such as bacterial colonies [33,35] and epithelial monolayers [36]. Here, we report yet another feature of active defects: self-organization into stable like-charged bound pairs in the form of virtual full-integer defects-which has no parallel in equilibrium systems-and could be important in the formation of dynamically ordered stable structures in active systems.…”
mentioning
confidence: 99%
“…To investigate the formation of full-integer defects, we solve the full continuum equations of active nematohydrodynamics. This is commonly used in describing the spatiotemporal dynamics of a wide range of active systems, from microtubule-kinesin motor protein mixtures [21,48] and actin filaments powered by myosin motors [49], to bacterial colonies [35,50,51] and dense assemblies of fibroblast cells [52]. Within this framework, the dynamics of the active system is governed through the coupling between the evolution of a nematic tensor Q as the orientational order parameter and the velocity vector u as the slow variable.…”
mentioning
confidence: 99%
“…The constellation of topological defects and their dynamics within colonies of different bacterial morphologies have been described as two and three dimensional active nematic systems [51,[53][54][55]. Theoretically, the shape of growing bacterial colonies was explained using continuum approach wherein cells were treated as active gel growing in an isotropic liquid [53].…”
Section: Microbial Ecology: a Topological Perspectivementioning
confidence: 99%
“…Friction, between cells and with the underlying substrate, was found to be a key determinant of the defect dynamics, which ultimately regulated the colony morphology. Growth of bacterial monolayers under soft agarose surfaces demonstrated that topological defects were created at a constant rate, with the motility of +1/2 defects biased toward the colony periphery [54]. More recently, studies on bacterial monolayers were extended to analyze multilayer morphologies, capturing the early developmental stages of bacterial biofilms [51,55,56].…”
Section: Microbial Ecology: a Topological Perspectivementioning
confidence: 99%